2021
DOI: 10.1016/j.nlm.2020.107367
|View full text |Cite
|
Sign up to set email alerts
|

Systemic HDAC3 inhibition ameliorates impairments in synaptic plasticity caused by simulated galactic cosmic radiation exposure in male mice

Abstract: Deep space travel presents a number of measurable risks including exposure to a spectrum of radiations of varying qualities, termed galactic cosmic radiation (GCR) that are capable of penetrating the spacecraft, traversing through the body and impacting brain function. Using rodents, studies have reported that exposure to simulated GCR leads to cognitive impairments associated with changes in hippocampus function that can persist as long as one-year post exposure with no sign of recovery. Whether memory can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 69 publications
3
11
0
Order By: Relevance
“…More recent studies have increasingly taken advantage of newly available multi-ion irradiation paradigms that more closely mimic the space environment, such as Galactic Cosmic Radiation (GCRsim). Studies to date have found that GCRsim reduced the firing frequency of neuronal action potentials and impaired hippocampus-dependent memory and hippocampal LTP in mice [43,44], and decreased social interaction, increased anxiety-like behaviors, and impaired social recognition in male mice, corresponding with synaptic loss in the hippocampus [36]. Our behavioral results with 56 Fe, which is a component of GCRsim, largely support these findings.…”
Section: Discussionsupporting
confidence: 86%
“…More recent studies have increasingly taken advantage of newly available multi-ion irradiation paradigms that more closely mimic the space environment, such as Galactic Cosmic Radiation (GCRsim). Studies to date have found that GCRsim reduced the firing frequency of neuronal action potentials and impaired hippocampus-dependent memory and hippocampal LTP in mice [43,44], and decreased social interaction, increased anxiety-like behaviors, and impaired social recognition in male mice, corresponding with synaptic loss in the hippocampus [36]. Our behavioral results with 56 Fe, which is a component of GCRsim, largely support these findings.…”
Section: Discussionsupporting
confidence: 86%
“…Until recently, technological limitations have prevented evaluation of more space-relevant combinations of radiation exposures on CNS function. However, previous work from our laboratory and from the laboratories of others identified risks to the CNS following exposure to simplified 5- or 6- beam GCR simulations [ 3 , 4 , 9 ]. To more accurately recapitulate the space radiation environment, NASA has now developed the capability to deliver a complex GCR Sim that includes 33 distinct beams, predominated by protons and 4 He particles of various energies, interspersed with infrequent beams of different heavy ions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work from our laboratory and from the laboratory of others identified risks to the CNS following exposure to simplified 5- or 6-beam GCR simulations [ 3 , 4 , 9 ]. The goal of our current study was to use this same realistic 33-beam GCR Sim exposure model as that used by Kiffer and colleagues [ 11 ] at a more space-relevant total dose, delivered either chronically or acutely, to gain an improved understanding of the CNS impairments that astronauts may face during deep space exploration.…”
Section: Introductionmentioning
confidence: 99%
“…These data are consistent with the SR-induced changes in the DNA methylation status within the hippocampus [ 30 , 31 , 32 , 33 , 34 ]. The biological significance of these methylation changes is quite pronounced since SR-induced loss of hippocampal-dependent memory updating and LTP within the hippocampus were reversed by the use of histone deacetylase 3 inhibitors [ 35 ].…”
Section: Introductionmentioning
confidence: 99%